What Drives Ego Involvement in Young Customers’ Behaviour to Purchase Secondhand Clothes? - Prakoso, Fajar Adi; Suroso, Agus; Novandari, Weni (International Review of Management and Marketing, 2026)
Clothes are a means of self-expression for young consumers when buying secondhand clothes. Buying secondhand clothes is inseparable from a person's ego and sense of identity. However, studies on ego involvement are minimal and need further exploration. This study aims to discuss how ego-involvement factors influence loyalty and to reveal the character of young consumers when buying secondhand clothes, from the perspectives of brand image and consumer trust, using quantitative methods to test the influence of variables. The sample was selected from a survey of 259 respondents who had completed the survey and met the requirements, using purposive sampling. The study used Smart PLS to test proposed relationships among brand image, trust, ego involvement, and loyalty. The results of the study showed significant positive impacts on brand image to ego involvement, brand image to loyalty, ego involvement to loyalty, and trust to ego involvement and to loyalty. Ego involvement can influence young consumers' loyalty to buying secondhand clothes by fostering an emotional attachment and a strong value perception. All hypotheses are accepted and have a positive effect. Young consumers' emotional and psychological connection to self-expression drives ego involvement in purchasing secondhand clothing. Brand image and trust factors also influence this ego involvement and loyalty among young consumers.